2017
DOI: 10.3389/fevo.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

Mesosaurid Swim Traces

Abstract: Despite subaqueous fossils tracks of tetrapods being quite common in the fossil record, few studies discuss their classification and morphofunctional interpretation. Even with their simple morphology, some important information about the trackmakers can be retrieved from these tracks. Subaqueous traces were found in Brazil in the Irati Formation (Cisuralian, Permian), Paraná Basin, and described as Mesosaurichnium natans, related to Mesosauridae. The traces were produced in a shallow marine environment, whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(68 reference statements)
2
3
0
Order By: Relevance
“…Based on the large size (compare to Rossmann [ 10 , 14 ]), the absence of the suture which divides the procoracoid and metacoracoid in juveniles [ 30 ] and the presence of a well-ossified tarsus [ 31 ], the specimen is considered an adult [ 24 ]. This supports the view that lateral undulations of the trunk were not the key factor of locomotion in mesosaurs [ 2 , 24 , 32 – 35 ]. Possibly, their slow-paced swimming technique required only minor trunk flexibility or they mainly utilized the posterior portion of the vertebral column, using mostly the tail-driven propulsion, in a sub-carangiform (sub-anguilliform, axial subundulatory) fashion [ 2 , 24 , 32 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Based on the large size (compare to Rossmann [ 10 , 14 ]), the absence of the suture which divides the procoracoid and metacoracoid in juveniles [ 30 ] and the presence of a well-ossified tarsus [ 31 ], the specimen is considered an adult [ 24 ]. This supports the view that lateral undulations of the trunk were not the key factor of locomotion in mesosaurs [ 2 , 24 , 32 – 35 ]. Possibly, their slow-paced swimming technique required only minor trunk flexibility or they mainly utilized the posterior portion of the vertebral column, using mostly the tail-driven propulsion, in a sub-carangiform (sub-anguilliform, axial subundulatory) fashion [ 2 , 24 , 32 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…This supports the view that lateral undulations of the trunk were not the key factor of locomotion in mesosaurs [ 2 , 24 , 32 – 35 ]. Possibly, their slow-paced swimming technique required only minor trunk flexibility or they mainly utilized the posterior portion of the vertebral column, using mostly the tail-driven propulsion, in a sub-carangiform (sub-anguilliform, axial subundulatory) fashion [ 2 , 24 , 32 , 34 , 35 ]. This agrees with the speculation as to feeding habits of mesosaurs, which were shown to prey mostly on small, slow-moving pygocephalomorph crustaceans and occasionally scavenged on mesosaurid corpses [ 9 , 34 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…Mesosaurs are swimming reptiles, and the degree of involvement of the limbs in locomotion is still debated. Some authors support the idea of mainly tail-driven mesosaurs ( Braun & Reif, 1985 ; Villamil et al, 2016 ) while others suggested a potentially larger role of limbs in propulsion ( Da Silva & Sedor, 2017 ; MacDougall et al, 2020 ). Yet, the ontogenetic limb reduction we expose seems incompatible with the conception that limbs were crucial for locomotion.…”
Section: Discussionmentioning
confidence: 97%
“…1 ). This peculiar appearance has resulted in conflicting hypotheses about their ecology, from amphibious ( Núñez Demarco et al, 2018 ) to fully marine ( Modesto, 1999 ; Modesto, 2010 ; Canoville & Laurin, 2010 ), from undulatory ( Braun & Reif, 1985 ; Villamil et al, 2016 ) to partially limb-propelled swimmers ( Da Silva & Sedor, 2017 ; MacDougall et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rather than being a primarily tail driven swimmer as has been previously suggested 30 , mesosaurs could have used a combination of limbs and tail during aquatic locomotion, regardless of whether they were autotomizing their tails. Swim traces ascribed to mesosaurs have shown that while the tail was used in aquatic propulsion, the hind limbs would have also been used as a source of propulsion 45 . Overall, this suggests that, regardless of whether they could drop their tails or not, the limbs of mesosaurs would have played a larger role in aquatic locomotion than has previously been considered, something that warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%